2019
DOI: 10.3390/biom9040142
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Ligands as Helping Hands to L-DOPA in the Treatment of Parkinson’s Disease

Abstract: Levodopa (LD) is the most effective drug in the treatment of Parkinson’s disease (PD). However, although it represents the “gold standard” of PD therapy, LD can cause side effects, including gastrointestinal and cardiovascular symptoms as well as transient elevated liver enzyme levels. Moreover, LD therapy leads to LD-induced dyskinesia (LID), a disabling motor complication that represents a major challenge for the clinical neurologist. Due to the many limitations associated with LD therapeutic use, other dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 354 publications
(389 reference statements)
0
12
0
1
Order By: Relevance
“…So far, several reviews have been published that gathered information about the advances in the development of selective ligands [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Hamilton et al published a complex review that collects information about the rational drug design studies performed using QSAR, molecular docking, molecular dynamics and pharmacophore modeling, that were applied in the development of drugs against PD [ 52 ].…”
Section: Computational Approaches Used In the Development Of Novel Drugs Against Parkinson’s Diseasementioning
confidence: 99%
“…So far, several reviews have been published that gathered information about the advances in the development of selective ligands [ 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Hamilton et al published a complex review that collects information about the rational drug design studies performed using QSAR, molecular docking, molecular dynamics and pharmacophore modeling, that were applied in the development of drugs against PD [ 52 ].…”
Section: Computational Approaches Used In the Development Of Novel Drugs Against Parkinson’s Diseasementioning
confidence: 99%
“…The latter possibility is conceivable as >95% of striatal neurons are inhibitory and tightly coupled and so, like M1, may be capable of sustaining high-frequency gamma oscillations. Finally, it is conceivable that focal gamma is mediated by dopamine D4 receptors in the basal ganglia (Bello et al, 2019) as D4R-mediated gamma oscillations have been observed in the hippocampus (Andersson et al, 2012).…”
Section: Focal 80-hz Gamma Following High-dose L-dopa Primingmentioning
confidence: 99%
“…В качестве средства, способного корригировать леводопа-индуцированную дискинезию, предложено еще одно производное морфолина -VU6004461. Его механизм действия заключается в непосредственной активации D4-дофаминовых рецепторов [65], что роднит его с рядом противопаркинсонических препаратов, включающим прамипексол, ропинирол, перголид и бромокриптин [66]. У мышей с 6-ГД-моделью БП VU6004461 в дозах 10 и 20 мг/кг значительно уменьшал выраженность аномальных непроизвольных движений, связанных с приемом леводопы [67].…”
Section: Vu6004461unclassified